Her secret past with the Viscount - Martin, Laura (Laura Leanne) (Harlequin historicals., 2023)
As fellow survivors of a shipwreck and rescue from a remote island, seeing Lord Hugh Wilder again at a society party only rekindles Sylvia Thompson's feelings for the Viscount.